An analysis of four instructional strategies used by secondary school music teachers in Uganda. (May 2022) - Sekalegga, Lawrence Branco
This paper provides an analysis of how secondary school music teachers (N = 10) in Uganda apply instructional strategies (peer teaching, practical music-making, modeling, and feedback) in their music lessons. Analysis was undertaken to establish if there were any similarities or differences amongst the urban, suburban, and rural music teachers and between experienced and inexperienced teachers in ways they employed instructional strategies. Data were gathered through videotaped classroom observations and analyzed via SCRIBE (Simple Computer Recording Interface for Behavioral Evaluation). Results showed that practical music-making was the most observed strategy while negative feedback (disapprovals) was the least observed strategy. Experienced teachers provided more feedback in form of approval and engaged their students more in practical music-making activities. Results from the study are discussed in terms of implications for improved teacher preparation. The strategies discussed in this study should be encouraged through teacher professional development, and through greater emphasis in teacher preparation courses.